Gulf charities and Islamic philanthropy in the "age of terror" and beyond - Lacey, Robert; Benthall, Jonathan (Gerlach Press, 2014)
Gulf Charities and Islamic Philanthropy in the 'Age of Terror' and Beyond is the first book to be published on the charities of Saudi Arabia and the Arabian Gulf, covering their work both domestic and international. From a diversity of viewpoints, the book addresses: the historical roots of Islamic philanthropy in religious traditions and geopolitical movements; the interactions of the Gulf charities with "Western" relief and development institutions.